2019
DOI: 10.1021/acschembio.9b00639
|View full text |Cite
|
Sign up to set email alerts
|

Structural Basis for Finding OG Lesions and Avoiding Undamaged G by the DNA Glycosylase MutY

Abstract: The adenine glycosylase MutY selectively initiates repair of OG:A lesions and, by comparison, avoids G:A mispairs. The ability to distinguish these closely related substrates relies on the Cterminal domain of MutY which structurally resembles MutT. To understand the mechanism for substrate specificity, we crystallized MutY in complex with DNA containing G across from the high-affinity azaribose transition state analog. Our structure shows that G is accommodated by the OG site and highlights the role of a serin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
54
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 25 publications
(54 citation statements)
references
References 47 publications
0
54
0
Order By: Relevance
“…Within the active site, H-bonding contacts align the A with the catalytic Glu and Asp residues (Glu43 and Asp144 in Gs MutY, Glu37 and Asp138 in Ec MutY) orienting it for cleavage (Figure c) . Russelburg et al demonstrated that a C-terminal domain Ser (308 in Gs MutY), which forms a H-bond with the N7-H in OG, disengages from the N7 lone pair in the corresponding structure with G, suggesting one potential mechanism for discrimination between OG and G . Additionally, Wang et al have reported a cocrystal structure of MutY bound to its “antisubstrate” OG:C, wherein the entry of C into the active site is blocked to prevent accidental and promutagenic excision .…”
Section: Introductionmentioning
confidence: 99%
“…Within the active site, H-bonding contacts align the A with the catalytic Glu and Asp residues (Glu43 and Asp144 in Gs MutY, Glu37 and Asp138 in Ec MutY) orienting it for cleavage (Figure c) . Russelburg et al demonstrated that a C-terminal domain Ser (308 in Gs MutY), which forms a H-bond with the N7-H in OG, disengages from the N7 lone pair in the corresponding structure with G, suggesting one potential mechanism for discrimination between OG and G . Additionally, Wang et al have reported a cocrystal structure of MutY bound to its “antisubstrate” OG:C, wherein the entry of C into the active site is blocked to prevent accidental and promutagenic excision .…”
Section: Introductionmentioning
confidence: 99%
“…The sensitivity of MutY repair to the 8OI substitution suggests that specific structural motifs in MutY serve as “sensors” of interhelical OG:A bps through interactions with the 2-amino group of OG. In recent X-ray structural studies of Geobacillus stearothermophilus ( Gs ) MutY, we uncovered the importance of a highly conserved H 305 XFSH 309 loop within the C-terminal domain that tucks into the major groove proximal to the OG (Figure E). , Modeling using several Gs MutY structures suggests that H309 (H296 in E. coli ) may be appropriately positioned to detect the 2-amino group of OG syn (Figure S1). In the current study, we employed a combination of single-molecule (SM) fluorescence microscopy DNA search assays, in vitro glycosylase and binding measurements, and a plasmid-based cellular repair assay to investigate the search and repair behavior of E. coli wild-type (WT) and H296A MutY on OG:A and 8OI:A damage sites.…”
mentioning
confidence: 99%
“…The unexpected importance of the two singular positions of H296 and the 2-amino of 8OI for lesion detection points to a novel approach to develop allosteric inhibitors for MUTYH. 9 Inhibitors for MUTYH would be useful chemical biology probes and may potentially serve as cancer chemotherapeutics to reduce cancer cell proliferation or associated inflammatory responses. 18−21 ■ ASSOCIATED CONTENT * sı Supporting Information…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…BER DNA lesion recognition relies on the activity of specialized glycosylases, for example, the 8-oxoguanine-DNA N-glycosylase (OGG1; ECU08_0770 in E. cuniculi [ Gill and Fast 2007 ]), which senses guanines oxidized to 8-dihydro-7,8-oxoguanosine (8-oxodG) and removes them from DNA before downstream replication processes ( Chalissery et al 2017 ). Using a combination of structural homology and PSI-BLAST searches, we identified MUTYH (MutY homolog) as ECU08_0880 in E. cuniculi , a DNA glycosylase that removes adenines improperly paired to 8-oxodG ( Russelburg et al 2020 ). The HR pathway is an error-free DNA repair mechanism active in the S and G2 phases of the cell cycle that repairs double-stranded breaks using the sister chromatid DNA strand as a template ( Sun et al 2020 ), and whose components are known to interact with the ataxia-telangiectasia mutated kinase ( Zhou et al 2020 ).…”
Section: Resultsmentioning
confidence: 99%